Regulation of Lipid Droplet Cholesterol Efflux from Macrophage Foam Cells: a Role for Oxysterols and Autophagy - Ouimet, Mireille (Université d'Ottawa / University of Ottawa, 2011)
Macrophage foam cells are the major culprits in atherosclerotic lesions, having a prominent role in both lesion initiation and progression. With atherosclerosis being the main factor underlying cardiovascular complications, there is a long-standing interest on finding ways to reverse lipid buildup in plaques. Studies have shown that promoting reverse cholesterol transport (RCT) from macrophage foam cells is anti-atherogenic because it alleviates the cholesterol burden of the plaques. The goal of this thesis was to gain insight into the mechanisms that govern cholesterol efflux from macrophage foam cells. The first part of this study looked at the ability of different oxysterols to promote cholesterol efflux in unloaded as compared to lipid-loaded macrophages, and our major finding here is that epoxycholesterol decreases efflux in lipid-loaded macrophages. It appears that epoxycholesterol does so by impairing the release cholesterol from its cellular storage site, the lipid droplet (LD), where it accumulates in the form of cholesteryl esters (CE). These results highlighted the importance of cholesterol release from LDs for efflux; indeed, this process is increasingly being recognized as the rate-limiting step for RCT in vivo. Subsequent experiments aimed at elucidating the mechanisms that govern LD CE hydrolysis in macrophage foam cells lead to the discovery of a novel pathway involved in cholesterol efflux. Macrophage CE hydrolysis is classically defined as being entirely dependent on neutral CE hydrolases. In the second part of this study, we demonstrate that in addition to the canonical CE hydrolases, which mediate neutral lipid hydrolysis, lysosomal acid lipase (LAL) also participates in the hydrolysis of cytoplasmic CE. Autophagy is specifically triggered in macrophages by atherogenic lipoproteins and delivers LD CE to LAL in lysosomes, thus generating free cholesterol for efflux. This autophagy-mediated cholesterol efflux is a process that is primarily dependant on the ABCA1 transporter and, importantly, is important for whole-body RCT. Overall, the studies presented in this thesis support that macrophage LD CE hydrolysis is rate-limiting for cholesterol efflux and shed light on the mechanisms of cholesterol mobilization for efflux in macrophage foam cells.
Keywords: atherosclerosis; macrophage foam cell; lipolysis; cholesterol efflux; lipid droplet; autophagy